Habitat selection of cattle in a traditionally fire-managed landscape in the Bale mountains, Ethiopia - Arvidsson, Åsa (2009)
In the Ethiopian highlands farming often is the only income. Above 3 300 m elevation however, cultivation is limited by the fact that it often is below 0 ˚C during night. This makes it even more important to keep livestock for meet, milk and as the main income. If it was impossible to keep livestock it would be hard to make a living up in the mountains. When reaching 3 500 m elevation two species of Erica, Erica trimera and Erica arborea dominates the vegetation. If the Erica-bushes grow freely they can reach a height of 2 meters in less than 10 years. Cattle, sheep and goats can then not reach the branches to browse. To prevent the Erica to grow this tall and to make it re-sprout, the cattle owners burn the vegetation when necessary. This burning makes the landscape mosaic-looking with patches of different age class. This burning however is illegal. The purpose of my study was to analyze which age-classes the cattle use, and how they move during grazing. This can indicate whether burning is needed to maintain a productive rangeland. Every observation-session lasted maximum 4 hours and every time one cow was selected and each five minutes the activity of the cow and the age of the vegetation were noted. After making line transects on premade photomaps the access to the different age classes (time since burning) was made. The results showed that the time the cattle spent in one year old burns do not stand in proportion of the amount one year old vegetation available. Despite the fact that it is only 31% of the vegetation that is one year old the cattle spent as much as 44% of their time there. For three year old vegetation the time spent and the amount is almost equal, 26% of the observations were made in 3 years old and 28% of the vegetation is burnt three years ago. Forty-three % of the vegetation was classified as old; the cattle however only spent 19% of their time there. Further, the cattle had to pass by old vegetation to reach younger, it is therefore possibly that the cattle would spend even less time in old vegetation if they were free to choose. The cattle moved in herds with between 7 and 18 animals. While grazing they moved in a quite straight direction with an average speed of 0,25 km/h; mornings up the mountain and afternoons down to the settlements, often without being herded. Altogether the cattle moved around 3 kilometers per day. To add more information on the animal husbandry in the study area two interviews with cattle owners were made. To the cattle owners it was obvious that young Erica is the most important feeding source for their livestock. This study support their view; the traditional fire management seems to give the cattle in the area a good pasture and in that way make it possible for the inhabitants to maintain their living.